Strengthening the Role of Crafts as the Economic Drivers of Rural Communities in Sumberejo Village - Wulandari, Widah Fitri; Hanifuddin, Iza (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sumberejo Village is a village located in Sine sub-district, Ngawi Regency. Which is in a mountainous area. Dusun Ngasem itself has many assets in terms of community or social group, nature, knowledge, culture, physical, financial, personal. Interestingly, Ngasem Hamlet has several assets that are different from other hamlets in Sumberejo Village. The assets owned are the community assets of the bamboo booth craftsman group, the business of making bamboo booths is the community's livelihood. The method used is ABCD (Asset-Based Community Development) which prioritizes the utilization of existing assets and potentials around the community, namely the booth craftsman group. Based on the explanation of the ABCD approach, the skills improvement of the craftsmen and the addition of cubicle craftsmen in the strategy of running the business are obtained. With the progress of the business that can help the community in family life such as work, income / income, education.